Fire ash residues do not affect ecological functions of Phanaeus palaeno in Cerrado grassland - Reis, Nayara Letícia; Beiroz, Wallace; Peñaflor, Maria Fernanda Gomes Villalba; Louzada, Júlio (Entomologia experimentalis et applicata, 2023)
Fire is a major force acting on the structure and dynamics of the Cerrado (Brazilian savanna). Post‐fire conditions can be severe for soil‐dwelling organisms, such as dung beetles, which play essential roles in the Cerrado ecosystem. This study evaluated whether ash residues affect the ecological functions of dung burial and soil bioturbation by the Cerrado‐native beetle Phanaeus palaeno Blanchard (Coleoptera: Scarabaeidae, Phanaeini), and how its sex and weight influence the performance of ecological functions under post‐fire conditions. The beetles were collected from open natural grasslands and pastures in the Cerrado biome, and the functions performed by the individuals were evaluated in the laboratory. The response of beetles was measured by quantifying the amount of buried dung and soil by both females and males in buckets filled with soil, half covered or fully covered with ash, or in buckets without ash. The amount of buried dung or bioturbated soil did not differ among treatments, demonstrating that ash does not influence P. palaeno in performing these functions. Females bioturbated more soil and buried more dung than males, but neither were affected by ash. As dung beetles perform essential ecosystem functions, this information may be helpful in developing novel fire management practices to conserve Cerrado biodiversity. We tested whether fire ash deposited on the soil influences the ecological functions performed by the Cerrado‐native dung beetle Phanaeus palaeno (Coleoptera: Scarabaeidae). The ash did not influence dung burial nor bioturbation of soil by dung beetles. However, both functions were influenced by sex, females being more active than males. These results contribute to the understanding of the resilience of the native fauna to fire in savanna ecosystems such as the Brazilian Cerrado.